An Analysis of Accounts Receivable Control Strategies as a Financial Literacy Effort to Reduce Uncollectible Receivables at UD. ANA PALU - Mohamad Mahfud; Ruski (Global Action and Education for Society, 2025)
The purpose of this study is to examine the methods used by UD. ANA PALU, a trading company involved in the distribution of food and drinks, to reduce the quantity of accounts receivable that cannot be collected. This study used a case study methodology in conjunction with a qualitative approach. Techniques for gathering data included recordkeeping, interviews, and observation. The results of the study show that the primary reasons for uncollectible receivables are customers' malice in not making payments, payment delays brought on by an increase in rivals, and a lack of committed staff to manage receivables. The control strategies implemented include setting a maximum credit limit, tightening the payment deadline, and selectively approving customers eligible for credit. Although these strategies have successfully reduced the percentage of uncollectible receivables over time, further improvements are still needed. This study recommends strengthening credit policies, utilizing automatic payment reminder systems, and collaborating with financial institutions to mitigate payment failure risks.